A Qualitative Focus Group Study for the Exploration of Knowledge and Attitudes of Informal Caregivers Toward Breast Cancer: Perceptions of Informal Caregivers and Healthcare Professionals in Three European Countries - Tsitsi Theologia; Christou Andri; Christodoulou-Fella Maria; Beccati Sara; Boccaletti Licia; Palermo Alessia; Alves José; Teixeira Ana; Charalambous Andreas (SAGE PUBLICATIONS INC, 2022)
Breast cancer (BC) early screening and detection is a main component for the outcome of the treatment and overall survival. Informal caregivers (ICGs) are less likely to initiate early BC screening methods and utilize health services. The purpose of this study was to explore ICGs' knowledge and perceptions, including educational and training opportunities or barriers, in promoting early detection practices for BC, as well as healthcare professionals' (HCP) respective perceptions concerning ICGs in order to identify the need of selected health literacy interventions. A qualitative focus group study was implemented in 3 European countries, using a purposive sampling technique. In total, 26 ICGs and 18 HCPs were involved. The themes that emerged from the focus groups interviews included knowledge, perceptions, attitudes, and beliefs concerning BC; motivational factors and barriers that influence early screening practices and personal involvement. Motivators and barriers concerning BC screening adherence were linked to knowledge, beliefs and perceptions. Health promotion strategies and user-friendly tools should be developed, targeting on the implementation of BC early detection practices among informal caregivers.